(untitled) (World Science, 2019)
The work, presented below, compares pathomorphological changes of the articular cartilage in the distal epiphysis of the femur and proximal epiphyses of the tibia at the end of the 56th day in rats after two - week opioid withdrawal at the micro- and ultrastructural levels. The goal was achieved by micro- and ultrastructural visualization of the components of the articular cartilage. Specimen preparation for electron and light microscopy was done according to the generally accepted methods. The results of this study will form the basis for developing a comprehensive therapeutical approach in management of lesions of structural components of the articular cartilage in opioid chondrodystrophy.